2011
DOI: 10.1080/00222933.2011.558640
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and distribution of the genusAmphicteis(Polychaeta: Ampharetidae) collected by the BIOICE project in Icelandic waters

Abstract: Based on material collected during the BIOICE project off Iceland, four species of polychaetous annelids belonging to the genus Amphicteis Grube, 1850 (Polychaeta: Ampharetidae) were found: Amphicteis gunneri, Amphicteis ninonae, Amphicteis vestis and Amphicteis wesenbergae sp. nov. The differences between A. gunneri and A. ninonae, two species usually confused in the literature, are reviewed. Amphicteis vestis is described from newly collected material and its taxonomy in relation to other ampharetid taxa wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…For comparison purposes, type material of Amphicteis wesenbergae Parapar et al, 2011 and other specimens from selected species were studied by authors during several research stays in the Sandgerdi Marine Centre, Iceland (IMNH) and the Zoological Museum, University of Copenhagen, Denmark (ZMUC). Species descriptions and terminology follow Hartley (1985), Holthe (1986a, b), Jirkov (2008, Reuscher et al (2009), Parapar et al (2011Parapar et al ( , 2012 and Imajima et al (2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison purposes, type material of Amphicteis wesenbergae Parapar et al, 2011 and other specimens from selected species were studied by authors during several research stays in the Sandgerdi Marine Centre, Iceland (IMNH) and the Zoological Museum, University of Copenhagen, Denmark (ZMUC). Species descriptions and terminology follow Hartley (1985), Holthe (1986a, b), Jirkov (2008, Reuscher et al (2009), Parapar et al (2011Parapar et al ( , 2012 and Imajima et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…21 according to Jirkov (2011) or 73 and 71 according to Salazar & Hutchings (2012) and Reuscher et al (2009), respectively). Since papers by Hartley (1985) and Holthe (1986a, b), knowledge of this family has had significant contributions, from Mackie & Pleijel (1995), Jirkov (2001 and Parapar et al (2011Parapar et al ( , 2012 for European waters, and from Hilbig (2000), Holthe (2000), Jirkov (2008), Schüller (2008), Reuscher et al (2009) and Imajima et al (2012Imajima et al ( , 2013 for other oceans.…”
Section: Introductionmentioning
confidence: 99%
“…In total, 29 species of ampharetids have been reported up to date in Icelandic waters from BIOICE material, including the two new species recently described by Parapar et al (2011cParapar et al ( , 2012 and the new records reported in this paper. Further work is, however, needed to assess the true identity of some taxa with wide distri− bution range across the Arctic and other oceans, and therefore the actual diversity of this family in Iceland.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies on this family were already done dealing respectively with the genus Amphicteis Grube, 1850 (Parapar et al 2011c) and Ampharete Malmgren, 1866 . Here, we report sev− enteen additional species belonging to eleven genera and provide comments about their taxonomy, distribution and ecology in Iceland.…”
Section: Introductionmentioning
confidence: 99%
“…Large programs such as BIOICE around Iceland (e.g. Parapar et al, 2011), and benthic studies in Greenland (Sejr et al, 2010), are in the process of filling other prominent regional gaps. Ironically, nearshore waters remain poorly studied across most of the Arctic, with most of our knowledge derived from a handful of well-established marine stations such as those in Hornsund and Kongsfjorden in Svalbard.…”
Section: Status On Current Knowledge Of Arctic Benthic Biodiversitymentioning
confidence: 99%